PENERAPAN MATERIAL REQUIREMENT PLANNING (MRP) GUNA PERENCANAAN PERSEDIAAN BAHAN BAKU SANITIZER TISSUE PADA CV. COOL CLEAN MALANG - Aquarista Yulia Wardani; Dewi Siswanti (Sekolah Tinggi Teknik Malang, 2018)
CV. Cool Clean Malang is a company engaged in wet tissue industry. Products that undergo many orders or requests are Aqua's tissue sanitizer products. Planning of raw material inventory is the main thing to do. When inventory planning is not done, it will be detrimental to the company due to the cost of inventory due to shortage inventory or overstock. The purpose of this research is to know the application of material requirement planning (mrp) for the planning of raw material sanitizer tissue to avoid overstock or shortage of CV. Cool Clean Malang. The results of this study that the cost of inventory owned by the company when following the method applied by the company is higher than the method of MRP (Material Requirement Planning) with lot size lot for lot. Lot size with lot for lot produces the minimum cost compared to LUC method and Silver Meal is Rp. 6.930.000, - for the material of tissue paper, Rp. 5.720.000, - for packaging raw materials and Rp. 3.960.000, - for raw materials of alcohol. The cost of inventory is very influential with the company's capital. And the average quantity of inventory that the company keeps when following the method applied by the company is higher than the least square planning method. The average quantity of inventory is very influential with the cost of inventory borne by the company. The difference is the cost of ordering and the amount of inventory is stored.Keywords: MRP, Lot Sizing, Inventory Planning